Intellectual capital management in performing arts: A case study - Matos, F.; Matos, N. (Proceedings of the 25th European Conference on Knowledge Management, ECKM 2024, 2024)
he permanent search for organizational competitiveness in a context marked by sustainability objectives and digital transformation leads companies to develop management tools and models that guarantee them a high level of competition. Understanding intellectual capital management (ICM) processes in the different areas of business activity is, therefore, a priority for creating value. This research aims to analyse ICM through an audit of its main dimensions and try to understand its relationship with knowledge management processes, namely the retention and transfer of knowledge in an area that still needs to be explored: the performing arts industry. The performing arts, also known as 'creative experience providers', are professional areas based on arts and culture, which are based on selling cultural shows (e.g., theatres, ballet companies, orchestras) and whose professional activity is acting for audiences. The research methodology is based on a case study carried out in a Portuguese performing arts organization. The theoretical support model was an intellectual capital management model previously tested in companies with a different profile than these organizations. The main findings point out that intellectual capital management in the performing arts industry can be audited. However, adjustments must be made to these industries' working realities. It was also concluded that intellectual capital management is a critical factor in the success and survival of these industries, so the management of this asset and its valorization is strategic. The uniqueness of this study is its contribution to stimulating data-driven discussions regarding the necessity of improving intellectual capital management practices in organizations, with particular emphasis on organizations such as those in the performing arts sector, where the most significant value is centred on the intangible assets of each worker.